2004
DOI: 10.1300/j001v23n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Group Culture and Patterns of Interaction in Psychotherapy Supervision Groups

Abstract: Beginner supervisees (n = 84) and their psychotherapy supervisors who worked in 28 supervision groups in an academic training context participated in this study. SYMLOG self-ratings of actual and ideal experiences of the group interactions were collected at three measurement points: the beginning, middle, and end of the supervision. The main purpose was to examine group members' (supervisees and supervisors) experiences of patterns of polarization in terms of development of subgroups within the supervision gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…A previous study (Ögren & Sundin, 2005) showed that the factor solution was stable and that the scale had acceptable internal consistency (α = .82).…”
Section: Attained Psychotherapeutic Knowledge and Skillsmentioning
confidence: 90%
See 2 more Smart Citations
“…A previous study (Ögren & Sundin, 2005) showed that the factor solution was stable and that the scale had acceptable internal consistency (α = .82).…”
Section: Attained Psychotherapeutic Knowledge and Skillsmentioning
confidence: 90%
“…Empirical studies of differences in perceived knowledge attainment and group interaction (Sundin & Ögren, submitted b;Ögren & Sundin, 2005) and group climate (Sundin & Ögren, submitted a) in supervisees admitted by an interview and by the traditional procedure respectively suggested that both groups of supervisees attained a substantial amount of knowledge, developed more stable and mature relations to the supervisor and peers, and a more beneficial group climate over time.…”
Section: Changes Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Each respondent received a cover letter, in which group supervision was deflned (Bernard & Goodyear, 2009), institutional review board considerations were outlined, and reassurance was given that responses would be anonymous. The supervisor and supervisee surveys were parallel forms of the same instrument, based on the original ethics survey developed by Pope et al (1987), and were divided into three main parts.…”
Section: Survey Questionnairementioning
confidence: 99%
“…At the other end of the continuum, group supervision is less structured and more process focused, with members encouraged to self-disclose regarding their professional anxieties and their countertransference reactions to clients, and to share with feedback one another regarding the dynamics of the supervision group interactions. This group style has been referred to as relationship oriented (Ögren et al, 2002) or process-oriented (e.g., Bernard & Goodyear, 2009). In practice, most group supervision does not fit squarely at either end of the spectrum but includes elements of both structured activities, like case presentations and process-based discussions, regarding interpersonal dynamics and affective responses (Riva & Cornish, 2008).…”
mentioning
confidence: 99%